B cell clonality in gastric lymphoid tissues of patients with Sjögren's syndrome. Issue 5 (May 1996) - Ferraccioli, G F; Sorrentino, D; De Vita, S; Casatta, L; Labombarda, A; Avellini, C; Dolcetti, R; Di Luca, D; Beltrami, C A; Boiocchi, M; Bartoli, E
Abstract : OBJECTIVE: To determine the prevalence of mucosa associated lymphoid tissue (MALT) in the stomach and of a possible antigen driven proliferation, in patients with Sjögren's syndrome (SS). METHODS: Twenty one patients with primary SS and 80 dyspeptic controls underwent upper endoscopy. Lymphoid tissue and Helicobacter pylori were assessed by histopathological analysis. Epstein-Barr virus (EBV) or human herpes virus-6 (HHV-6) genome were studied by polymerase chain reaction (PCR) DNA amplification. Two PCR VDJ procedures were used to detect immunoglobulin heavy chain (IgH) gene rearrangement. RESULTS: Organised MALT was found in 33.3% of the patients, compared with 21.5% of the controls (NS). H pylori infection was seen in 71% of patients and 63% of controls. Genomic EBV or HHV-6 was found in a minor portion of SS gastric tissues. B cell expansion was detected in nine of the 21 patients. Infectious agents in the stomach might have contributed to B cell clonality only in 55.5% of the cases. No strict relationship was found between lymphoid follicles and clonality. CONCLUSION: Lymphoid accumulation in the gastric mucosa is common in Sjögren's syndrome, but full evidence for an antigen driven B cell expansion could not be demonstrated. Only a portion of those with clonal B cell expansion had evidence of an infectious agent. Other unknown infectious agents or factors related to the underlying disease (autoantigen) and its tissue environment may have a further role as possible causes of B clonal expansion in the gastric mucosa.